LOMBA TAHFIDZ SEBAGAI MEDIA PEMBINAAN IBADAH ANAK TPQ OLEH MAHASISWA KKN STITNU SAKINAH DHARMASRAYA DI MASJID BAITURRAHMAN NAGARI BLOK A KURNIA - gofrinaldo; Imran, Ali; Diyas, Sultan; Syah Rifai, Adrian; Ulpi, Kurni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Religious practice development for TPQ-aged children is an essential aspect in strengthening their religious character from an early age. This study aims to describe the implementation of the tahfidz competition organized by the KKN students of STITNU Sakinah Dharmasraya at Baiturrahman Mosque, Nagari Blok A Kurnia, as a medium for fostering worship habits among TPQ children. This research employs a qualitative descriptive approach through activity observation, documentation, and interviews with the committee and TPQ instructors. The findings show that the tahfidz competition not only increases children’s motivation in memorizing the Qur’an but also strengthens their worship discipline, courage to perform, and self-confidence. The activity also received full support from the community and mosque administrators. The tahfidz competition proves to be an effective medium for cultivating children’s love for the Qur’an and other worship practices